Dopaminergic Neuroprotection with Atremorine in Parkinson´s Disease - Carrera, Ivan; Fernandez-Novoa, Lucia; Sampedro, Carolina; Tarasov, Vadim V.; Aliev, Gjumrakch; Cacabelos, Ramon (Current Medicinal Chemistry, 2018)
Patients with Parkinson’s disease (PD) are looking forward to new therapeutic strategies that may gradually decelerate the rate of neurodegenerative decline, associated with mobility restrictions and related morbidity. Its continuous neurodegenerative process, exacerbated by genetic mutations or environmental toxins, involves a progressive reduction in the dopamine neurotransmission levels, synaptic uptake density, oxidative glucose intake, deficient striatal lactate accumulation and chronic inflammation. Over the last decade, novel bioproducts have received considerable interest due to their unique potential of unifying nutritional, safety and therapeutic natural effects. Some nutraceuticals play a crucial role in the control of the signaling transduction pathways in neurotransmission and inflammation affected in PD, and some natural compounds can beneficially interact with each one of these biological mechanisms to slow down disease progression. Atremorine, a novel plant-derived nutraceutical, probably with a neuroprotective effect in the dopaminergic neurons of the substantia nigra (pars compacta), is a prototype of this new category of bioproducts with potential effects in PD. The major focus of this review will be on the current knowledge and biomedical investigation strategies through a plant-derived neuroprotective approach to improve life quality in PD patients, being of paramount importance for health providers, caregivers and the patients themselves.
Keywords: biotherapy